Impact of Technology, Military, and Socio-Economic Welfare on Conflict in Indonesia and Japan - Alwan Mubarok; Hikmat Zakky Almubaroq; Surachman Surjaatmadja; Agung Risdhianto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Conflicts are driven by various factors, but over time, conflicts have evolved in nature and complexity. In addition to traditional factors, the emergence of technology has played a significant role in shaping conflicts. Technological advancements also have been a driving force in shaping societies and economies, and impacting various sectors and aspects of life. Our research uses Structural Equation Model (SEM) analysis. We will analyze the direct and indirect impacts of digital connectivity, technology trade, military expenditure and personnel, and socio-economic welfare on conflicts and tensions in Indonesia and Japan. The findings of our study suggest that technology variables such as digital connectivity and technology trade have a positive effect on socio-economic welfare in Indonesia with coefficients 0.311 and 0.457. A similar thing also happened in Japan with coefficients 1.312 and 0.310. However, technology trade can increase conflicts and tensions in Indonesia with coefficients 0.796, and digital connectivity can increase conflicts and tensions in Japan with coefficients 0.761. Additionally, socio-economic welfare significantly reduces conflict in Japan.